Conservation of the rare Astragalus tragacantha on the French Mediterranean coast: A case study of factors leading to transplantation success - Lucie Miché; Teddy Baumberger; Fatma Mirleau; Pascale Prudent; Marie Armange; Pascal Mirleau; Isabelle Laffont-Schwob; Thierry Tatoni; Lidwine Le Mire Pecheux; Antonin Dupin; Laureen Keller; Alex Baumel; et al. (Ecological Engineering, 2026)

Novel brominated flame retardants relevant for European aquatic environments: ranking of analytes to monitor and focus on the French Eastern Mediterranean coastline - Camille Rigal; Laurence Asia; Stéphanie Lebarillier; Pierre Doumenq; Pascal Mirleau; Laure Malleret (Environmental Science and Pollution Research, 2024)

Effect of an organophosphorus insecticide, soil texture and earthworm species on the turnover of soil, gut and cast microbiota during the earthworm's gut transit - Pascal Mirleau; Fatina Jouni; Juliette Chappat; Christophe Mazzia; Juan Carlos Sanchez-Hernandez; Yvan Capowiez; Magali Rault (Soil Biology and Biochemistry, 2024)

Extreme and Heterogeneous Conditions of the Desert Wetland Chott Ech Chergui (Algeria) Allow Isolating Halophilic, Alkalophilic and Thermophilic Bacteria - Aicha Mehirou Zouggar; Pascal Mirleau; Anne Chenuil; Francoise Denis; Aurore Caruso; Sidi Mohammed El Amine Abi Ayad; Sid Ahmed Chawki Lamara (Wetlands, 2023)

Preen gland removal increases plumage bacterial load but not that of feather-degrading bacteria - Gábor Árpád Czirják; Péter László Pap; Csongor István Vágási; Mathieu Giraudeau; Cosmin Mureşan; Pascal Mirleau; Philipp Heeb (The Science of Nature, 2013)

The role of immigration and in‐situ radiation in explaining blood parasite assemblages in an island bird clade - JOSSELIN CORNUAULT; ANAÏS BATAILLARD; BEN H. WARREN; AMÉLIE LOOTVOET; PASCAL MIRLEAU; THOMAS DUVAL; BORJA MILÁ; CHRISTOPHE THÉBAUD; PHILIPP HEEB (Molecular Ecology, 2012)
Parasite communities on islands are assembled through multiple immigrations and/or in‐situ diversification. In this study, we used a phylogenetic approach to investigate the role of such processes in shaping current patterns of diversity in Leucocytozoon , a group of haemosporidian blood parasites infecting whites eyes ( Zosterops ) endemic to the Mascarene archipelago (south‐western Indian Ocean). We found that this parasite community arose through a combination of multiple immigrations and in‐situ diversification, highlighting the importance of both processes in explaining island diversity. Specifically, two highly diverse parasite clades appear to have been present in the Mascarenes for most of their evolutionary history and have diversified within the archipelago, while another lineage apparently immigrated more recently, probably with human‐introduced birds. Interestingly, the evolutionary histories of one clade of parasites and Indian Ocean Zosterops seem tightly associated with a significant signal for phylogenetic congruence, suggesting that host–parasite co‐divergence may have occurred in this system.

Sexually transmitted bacteria affect female cloacal assemblages in a wild bird - Joël White; Pascal Mirleau; Etienne Danchin; Hervé Mulard; Scott A. Hatch; Philipp Heeb; Richard H. Wagner (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1515–1524 Abstract Sexual transmission is an important mode of disease propagation, yet its mechanisms remain largely unknown in wild populations. Birds comprise an important model for studying sexually transmitted microbes because their cloaca provides a potential for both gastrointestinal pathogens and endosymbionts to become incorporated into ejaculates. We experimentally demonstrate in a wild population of kittiwakes ( Rissa tridactyla ) that bacteria are transmitted during copulation and affect the composition and diversity of female bacterial communities. We used an anti‐insemination device attached to males in combination with a molecular technique (automated ribosomal intergenic spacer analysis) that describes bacterial communities. After inseminations were experimentally blocked, the cloacal communities of mates became increasingly dissimilar. Moreover, female cloacal diversity decreased and the extinction of mate‐shared bacteria increased, indicating that female cloacal assemblages revert to their pre‐copulatory state and that the cloaca comprises a resilient microbial ecosystem.

Aromatic plants in nests of the blue tit Cyanistes caeruleus protect chicks from bacteria - Adèle Mennerat; Pascal Mirleau; Jacques Blondel; Philippe Perret; Marcel M. Lambrechts; Philipp Heeb (Oecologia, 2009)

The LysR‐type regulator SftR is involved in soil survival and sulphate ester metabolism in Pseudomonas putida - Antje Kahnert; Pascal Mirleau; Robin Wait; Michael A. Kertesz (Environmental Microbiology, 2002)
Summary Sulphate esters make up a large proportion of the available sulphur in agricultural soils, and many pseudomonads can desulphurize a range of aryl‐ and alkylsulphate esters to provide sulphur for growth. After miniTn 5 transposon mutagenesis of Pseudomonas putida S‐313, we isolated 19 mutants that were defective in cleavage of the chromogenic sulphate ester 5‐bromo‐4‐chloro‐3‐indoxylsulphate (X‐sulphate). Analysis of these strains revealed that they carried independent insertions in a gene cluster that comprised genes for a sulphate ester/sulphonate transporter ( atsRBC ) a LysR‐type regulator ( sftR ), an oxygenolytic alkylsulphatase ( atsK ), an arylsulphotransferase ( astA ) and a putative TonB‐dependent receptor ( sftP ). The SftP protein was localized in the outer membrane, and the arylsulfphotransferase was identified as an intracellular enzyme. Expression of sftR was repressed in the presence of inorganic sulphate, and the sftR gene was required for the expression of atsBC , atsRK and sftP–astA . An sftR mutant was unable to grow with aryl‐ or alkylsulphate esters in laboratory media and showed significantly reduced survival compared with the parent strain during incubation in Danish agricultural and grassland soils. This effect suggests that sulphate esters are an important sulphur source for microbes in aerobic soils and highlights the importance of the microbial population in the soil sulphur cycle.